KEBIJAKAN KURIKULUM PAUD INDONESIA DARI MASA KE MASA - Yani Suryani; Dyah Khoirunnisa; Diah Andhika Sari (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
ABSTRACT Curriculum is the core of an educational process. This research examines the development of Early Childhood Education (ECE) curriculum policies in Indonesia over time. Using literature study methods and document analysis, this research traces significant changes in ECE curriculum policies from the independence era to the present. The results show that the ECE curriculum in Indonesia has undergone several changes, reflecting the evolving understanding of early childhood education and changes in socio-political contexts. To illustrate the background of this research, consider the journey of a young child in Indonesia, from the post-independence era when there was no specific ECE policy, to today's integrated approach focusing on character education and early literacy-numeracy skills. This evolution mirrors the nation's growth and changing priorities in education. This study aims to examine and understand the dynamics of changes in the education system, assess the effectiveness of learning approaches, and identify factors influencing curriculum transformation. The early post-independence period was marked by the absence of specific policies for ECE. It was only in the 1990s that ECE began to receive special attention with the issuance of various related policies. The 2004 curriculum marked a new era with a competency-based approach. The 2013 ECE curriculum then introduced a thematic-integrative approach and emphasis on character education. Recent developments show efforts to integrate play-based learning and strengthen early literacy-numeracy. ECE curriculum policies in Indonesia have developed progressively, but still face challenges in implementation and equitable access. Recommendations are provided for developing ECE curriculum policies that are more responsive to children's needs and Indonesia's local context. Keywords: Early Childhood Education, Indonesian curriculum policy, educational development